A randomized controlled trial of a coping-focused family resilience intervention program for breast cancer patients: Study protocol - Gao, Jie; Li, Jia-Xin; Chen, Wei-Ying; Song, Jiang-Yan; Zhou, Meng-Ke; Zhang, Shan-Shan; Li, Hui-Ping (Frontiers in Psychology, 2022)
Background: Breast cancer patients and their families are under various pressures in the process of disease diagnosis and treatment, which seriously threaten their physical and mental health. Findings from existing research suggest that good family resilience can help breast cancer families better adapt and cope with adversity and challenges. However, there are few intervention studies on family resilience, and no intervention studies on family resilience in breast cancer patients. Therefore, it is necessary to take appropriate measures to improve the resilience level of breast cancer families and help them better cope with the disease. Objective: The purpose of this study protocol is to demonstrate a coping-focused family resilience intervention to increase the level of family resilience in families with breast cancer and help them cope better with adversity. The effectiveness and feasibility of the intervention will be verified through a randomized controlled trial. Methods: The trial will recruit 170 breast cancer families and randomly assign them to experimental and control groups in a 1:1 ratio. The control group will receive routine care, and the intervention group will receive a 6-week one-on-one family resilience network intervention on the basis of the control group. Two groups of subjects will be assessed at baseline, and at 1 week, 1 month, and 3 months after the intervention. The primary outcome is family resilience, and the secondary outcomes are coping style, social support, family disease burden, and levels of anxiety and depression. Expected results: We hypothesized that after the intervention, the intervention group had significantly higher levels of family resilience compared with the pre-intervention and control group. In the intervention group, other aspects related to family resilience, such as family disease burden, anxiety and depression levels of patients and their families, were significantly alleviated, and disease coping and social support levels were also improved accordingly. Discussion：If the program is effective, it can help breast cancer families identify family strengths and resources to proactively address challenges so families can successfully navigate the crisis and facilitate patient and family recovery. It also provides a practical path for clinical workers to help breast cancer families adjust rationally.